Efficacy, Safety, and Economics of Intravenous Levetiracetam for Status Epilepticus: A Systematic Review and Meta-Analysis - Zhan-Miao Yi; Zhan-Miao Yi; Zhan-Miao Yi; Xu-Li Zhong; Ming-Lu Wang; Ming-Lu Wang; Yuan Zhang; Suo-Di Zhai; Suo-Di Zhai (Frontiers Media S.A., 2020)
ObjectiveTo evaluate efficacy, safety, and economics profiles of intravenous levetiracetam (LEV) for status epilepticus (SE).MethodsWe searched PubMed, Embase, the Cochrane Library, Clinicaltrials.gov, and OpenGrey.eu for eligible studies published from inception to June 12th 2019. Meta-analyses were conducted using random-effect model to calculate odds ratio (OR) of included randomized controlled trials (RCTs) with RevMan 5.3 software.ResultsA total of 478 studies were obtained. Five systematic reviews (SRs)/meta-analyses, 9 RCTs, 1 non-randomized trial, and 27 case series/reports and 1 economic study met the inclusion criteria. Five SRs indicated no statistically significant difference in rates of seizure cessation when LEV was compared with lorazepam (LOR), phenytoin (PHT), or valproate (VPA). Pooled results of included RCTs indicated no statistically significant difference in seizure cessation when LEV was compared with LOR [OR = 1.04, 95% confidence interval (CI) 0.37 to 2.92], PHT (OR = 0.90, 95% CI 0.64 to 1.27), and VPA (OR = 1.47, 95% CI 0.81 to 2.67); and no statistically significant difference in seizure freedom within 24 h compared with LOR [OR = 1.83, 95% CI 0.57 to 5.90] and PHT (OR = 1.08, 95% CI 0.63 to 1.87). Meanwhile, LEV did not increase the risk of mortality during hospitalization compared with LOR (OR = 1.03, 95% CI 0.31 to 3.39), PHT (OR = 0.89, 95% CI 0.37 to 2.10), VPA (OR = 1.28, 95% CI 0.32 to 5.07), and placebo (plus clonazepam, OR = 0.73, 95% CI 0.16 to 3.38). LEV had lower need for artificial ventilation (OR = 0.23, 95% CI 0.06 to 0.92) and a lower risk of hypotension (OR = 0.15, 95% CI 0.03 to 0.84) compared to LOR. A trend of lower risk of hypotension and higher risk of agitation was found when LEV was compared with PHT. Case series and case report studies indicated psychiatric and behavioral adverse events of LEV. Cost-effectiveness evaluations indicated LEV as the most cost-effective non-benzodiazepines anti-epileptic drug (AED).ConclusionsLEV has a similar efficacy as LOR, PHT, and VPA for SE, but a lower need for ventilator assistance and risk of hypotension, thus can be used as a second-line treatment for SE. However, more well-conducted studies to confirm the role of intravenous LEV for SE are still needed.